A Zirconia‐Nanoparticles‐Modified Carbon Paste Electrode for Voltammetric Determination of Ibuprofen. Issue 48 (20th December 2022) - Stoytcheva, Margarita; Zlatev, Roumen; Velkova, Zdravka; Gochev, Velizar; Valdez, Benjamin; Curiel, Mario
Abstract: Zirconia‐modified carbon paste electrode (ZrO2 /CPE) was prepared, characterized, and applied for efficient ibuprofen quantification by differential pulse adsorptive stripping voltammetry. The increased surface area of the modified electrode (up to 74 %), combined with the excellent zirconia adsorption performance allowed a 36 % signal increase to be achieved compared to bare CPE. Under optimized experimental conditions (69 : 1 w % graphite to ZrO2 ratio, 5 min accumulation time, pH 4.5) the ZrO2 /CPE exhibited a linear response to ibuprofen in the range from 20 μmol L −1 to 250 μmol L −1 . The LOD of 4 μmol L −1 (S/N=3) attained was found to be sufficient to perform ibuprofen analysis in pharmaceutical formulations. The results were validated by ibuprofen determination in commercial tablets with satisfactory recovery values (98.8–102 %). The presence of common pharmaceutical excipients did not affect the ibuprofen voltammetric response. The proposed sensor also demonstrated good reproducibility (RSD=2.84 %) and long term stability. Abstract : The enhanced analytical performances of the zirconia nanoparticles modified carbon paste electrode, as well as its low cost and simple fabrication and surface renewal procedures, make it suitable for the voltammetric determination of ibuprofen. It is an attractive alternative to previously utilized electrochemical platforms in drug analysis.